ELSA: Entropy-based local indicator of spatial association - Naimi, Babak; Hamm, Nicholas A.S.; Groen, Thomas; Skidmore, Andrew K.; Toxopeus, Albertus G.; Alibakhshi, Sara (Elsevier, 2019)
Research on spatial data analysis has developed a number of local indicators of spatial association (LISA), which allow exploration of local patterns in spatial data. These include local Moran’s I and local Geary’s c, as well as Gi and Gi* that can be used for continuous or interval variables only. Despite numerous situations where qualitative (nominal/categorical) variables are encountered, few attempts have been devoted to the development of methods to explore the local spatial pattern in categorical data. To our knowledge, there is no indicator of local spatial association that can be used for both continuous and categorical data at the same time.